Seeing through the other a study on image transference between former president Gloria Macapagal-Arroyo and the first gentleman Jose Miguel Arroyo - Mariano, June Abigael Z. (College of Mass Communication, University of the Philippines Diliman, 2012)
"This study explored the existence of image transference between former President Gloria Macapagal-Arroyo and her Spouse Jose Miguel Arroyo and the role of media in this process. Transference as defined in this study is the process of filling-in of gaps in present knowledge through the application of highly accessible and applicable attributes in his/her associative network to the less familiar spouse, indicated by the overlap of attributes ascribed to both spouses. Free-recall listing procedures of ascribed attributes (accessible constructs) about the spouses and explanation behind their trait ascriptions, as well as their thought processes in relating perception of the Spouses or reasons for citing common attributes between the spouses as a basis of applicability were obtained through qualitative methods (interviews and focus group discussion). Results of the study revealed that the media had been predominantly successful in enhancing accessibility of certain constructs (temper, work ethic and perceived corruption of GMA and negative behavioral attributes about FG) but the individual's existing schema in his/her associative memory network organize information from the media. As a caveat chronic and salient negatively framed news about the Spouses' behavioural attributes by some informants. COnversely, the informants rarely cited the media as a source directly stating negative affective attributes about the Spouses. Thus, negative affective trait ascription were rather a product of the informant's cognitive processing of information. Moreover, applicability is greatly attributed to the informant's cognitive processing. Most listed accessible attributes which may have resulted from chronicity enhanced by the media were not ascribed to both Spouses. Common attributes (ie., lavish, corrupt, intelligent) were cited for different reasons, taken from a different context and mentioned in the media reports. Informant's responses in the written test indicate that common attributes ascribed to the spouses may have been embedded in the media. Other competing schemas (husband and wife, expectations of leaders) also affect processing of information about the Spouses. Discussion and interviews revealed though processes other than transference such as 1) association based in metaphors about the family and the nation and presidential powers extending to her members of the family, 2) compartmentalized and distinct images held about the Spouses and 3) activation of other schema such as expectations of a good leader and the husband and wife partnership. These intricacies in information processing are indicatine of a well-defined knowledge structure about the Spouses. Implications of the study show the relevance of media's capacity to enhance accessibility, the intricacies of processing of information about Presidential Spouses, the explanatory value of cognitive approaches in social judgment and theoretical and methodological ramifications for studying transference."